Onn-widths of bounded periodic holomorphic functions - Wilderotter К. (Ukrains’kyi Matematychnyi Zhurnal, 1995)
The even-dimensional Kolmogorov widthsd 2n , Gel’fand widthsd 2n , and linear widths δ2n ofÃ inL q andC are determined exactly. We show that all threen-widths are equal and give a characterization of the widths in terms of Blaschke products.